2021
DOI: 10.1155/2021/5048375
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Taurine Combination Is Better Than Alone in Protecting Lipopolysaccharide‐Induced Mammary Inflammatory Lesions via Activating PI3K/Akt/mTOR Signaling Pathway by Scavenging Intracellular ROS

Abstract: Mastitis is mainly induced by gram-negative bacterial infections, causing devastating economic losses to the global cattle industry. Both selenium (Se) and taurine (Tau) exhibit multiple biological effects, including reducing inflammation. However, no studies have reported the protective effect of the combined use of Se and Tau against mastitis, and the underlying mechanisms remain unclear. In this study, lipopolysaccharide (LPS), the vital virulence factor of gram-negative bacteria, was used to construct the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Taurine, a main component in HYQT. Previous studies have found that taurine can regulate autophagy and regulate mTOR protein expression 30 . In this study, the effect of taurine on lipid accumulation in RAW 264.7 cells was detected.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Taurine, a main component in HYQT. Previous studies have found that taurine can regulate autophagy and regulate mTOR protein expression 30 . In this study, the effect of taurine on lipid accumulation in RAW 264.7 cells was detected.…”
Section: Resultsmentioning
confidence: 68%
“…Previous studies have found that taurine can regulate autophagy and regulate mTOR protein expression. 30 In this study, the effect of taurine on lipid accumulation in RAW 264.7 cells was detected. Furthermore, WB analysis was used to verify the regulation of taurine on lipophagy and mTORC1/TFEB signalling pathway.…”
Section: Resultsmentioning
confidence: 80%
“…This finding further confirms that TKT activity depends on FBXL6. Intercellular ROS scavenging can activate the mTOR pathway 37 , 38 . We found that treatment with the ROS inhibitor VAS2870 significantly increased the protein levels of PD-L1 and p-mTOR (whose downstream targets are p-S6K and p-4EBP1) and attenuated the TKT knockdown-mediated decreases in cell proliferation and migration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Selenium is an essential trace element in the body and exhibits various physiological functions, such as anti-inflammatory and antioxidant activities. Many clinical and basic studies have shown that selenium may relieve bovine mastitis by inhibiting the NF-κB and MAPK signaling pathways or activating NRF2 [ 92 , 93 , 94 , 95 , 96 ]. To further explore the molecular mechanism by which selenium alleviates mastitis, Jing et al analyzed the effect of selenium on exosomal RNA derived from MAC-T cells and determined the mRNA levels in exosomes derived from selenium-pretreated normal cells and from cells that had been infected with S. aureus [ 97 ].…”
Section: Exosomes Associated With Mastitismentioning
confidence: 99%